Long‐Term Outcome and Use of 6‐Minute Walk Test in West Highland White Terriers with Idiopathic Pulmonary Fibrosis. (13th January 2014) - Lilja‐Maula, L.I.O.; Laurila, H.P.; Syrjä, P.; Lappalainen, A.K.; Krafft, E.; Clercx, C.; Rajamäki, M.M.
<x xml:space="preserve">Abstract</x> Background Idiopathic pulmonary fibrosis (IPF) is an incurable interstitial lung disease occurring mainly in West Highland White Terriers (WHWTs). The effects of IPF on survival and on exercise tolerance in WHWTs are unknown. Objectives To evaluate survival, prognostic factors, and exercise tolerance in WHWTs with IPF. Animals Privately owned WHWTs; 15 with IPF and 11 healthy controls. Methods Prospective case‐control study conducted in 2007–2012. For survival, descriptive statistics and Kaplan–Meier (KM) survival curves with Cox proportional hazard ratios were performed. For the prognostic factor study, KM curves, Cox regression analysis, and logistic regression models were used. The 6‐minute walk test (6MWT) was used for measurement of exercise tolerance. Results The median IPF‐specific survival of deceased WHWTs (7/15) with IPF was 32 (range 2–51) months from onset of clinical signs. The risk of death from birth in WHWTs with IPF in age‐adjusted Cox model was significantly higher (hazard ratio 4.6; 95% confidence interval 1.05–19.74, P = .04) than in control WHWTs. No significant prognostic factors were identified. In 6MWT, WHWTs with IPF walked a shorter distance, median 398 m (range 273–519 m), than healthy controls, median 492 m (420–568 m), P = .05, and the partial pressure of oxygen in arterial blood in diseased dogs had a moderate positive correlation with walking distance (Kendall′s tau‐b = 0.69, P = .06). Conclusion and Clinical Importance IPF had a negative impact on life expectancy, but individual survival varied considerably. 6MWT proved to be a well‐tolerated, noninvasive test to evaluate exercise tolerance.